Transitions in frailty state 12 months after kidney transplantation: a prospective cohort study - dos Santos Mantovani, Milena [UNESP] (2022)
Background: Frailty is associated with several unfavorable outcomes after kidney transplantation (KTx). However, limited information is available regarding the transitions in frailty state and its components after KTx. This study aimed to evaluate the transitions in physical frailty phenotype and its components over a period of 12 months after KTx. Methods: In this prospective single-center cohort study, we measured physical frailty phenotype (PFP) and its components at the time of admission for KTx and 12 months after KTx. The evaluation includes five components: weakness (grip strength analysed by sex and body mass index quartiles), physical activity (kcals/week based on the Minnesota Leisure Time Physical Activity questionnaire), exhaustion (self-report using the Center for Epidemiological Studies Depression Scale), gait speed (time taken to walk 15 feet based on sex and height-specific cutoff), and unintentional weight loss (self-report of unintentional weight loss > 10 lbs in the last year). The exhaustion and physical activity components are validated in the Brazilian population. Each component is scored as 0 or 1 according to its presence or absence, and a PFP score of 3–5 defines frailty, 2 is intermediate, and 0–1 is rated as non-frail. We used the McNemar and Wilcoxon test to compare physical frailty phenotype and its components between the two periods. Results: Among 87 patients included in the study, 16.1% were classified as frail, 20.7% as intermediately frail, and 63.2% as non-frail. Sixty-four patients were included in the analysis to evaluate transitions in frailty. At the time of admission for KTx, 15.6% of patients were defined as frail compared to 4.7% of patients at 12 months after KTx (p = 0.023). Among the physical frailty phenotype components, the proportion of patients who scored in the weight loss category 12 months after KTx was significantly lower than that at the time of KTx (6.3% vs 34.4%, p < 0.001). Conclusions: There was a 69.9% reduction in the prevalence of frail patients at the end of the 12-month follow-up after KTx. Among the components of frailty, weight loss showed a significant improvement. Graphical abstract: [Figure not available: see fulltext.].